PENGEMBANGAN USAHA SOUVENIR “THEBEMBEB” BAHAN BAKU RESIN DI KOTA PANGKALPINANG - Ichsan Ananda Putra; Reza Widhar Pahlevi (Bajang Institute, 2022)
Nowdays, tourism is also a modern commodity which opens many new business opportunities. So that, it can become an support income for an area, especially the community with new jobs and business opportunities for the community. Tourism business opportunities that include culinary and souvenirs are two things that cannot be separated in supporting the tourism sector. If all elements of society synergize in terms of the development of the tourism sector, it is not impossible for the tourism sector to be the backbone of regional and national economic support. By increasing tourism sector, the presence of souvenirs